Comparison between Artisanal Fishery and Manila Clam Harvesting in the Venice Lagoon by Using Ecosystem Indicators: An Ecological Economics Perspective - Angela Granzotto; Fabio Pranovi; Simone Libralato; Patrizia Torricelli; Danilo Mainardi (Fondazione Eni Enrico Mattei (FEEM), 2004)
Artisanal fishery in the Venice lagoon is a multi-target activity with a long tradition. It was the main fishing activity till the late '80s when, after the introduction and spread of the Manila clam (Tapes philippinarum), the mechanical clam harvesting started. A mass-balance model of the lagoon ecosystem was developed using the Ecopath with Ecosim software. 73 scenarios, obtained by changing the fishing effort of the two different types of fishery, were used to explore their impact on the ecosystem. A set of indicators was applied in order to compare the two fishing activities. The results obtained showed that the two activities are strongly interlinked, even through they don't exploit the same resources. The mechanical clam harvesting could reasonably be considered to be the driving force; it is capable of determining the state of lagoon ecosystem. The above mentioned factors create a lot of conflict between the two types of fishery.
Keywords: Q01; Q22; 330; Artisanal fishery; Indicators; Dynamic model; Venice Lagoon; Fishing impact; Social and economic value